Incidence of leukaemia and lymphoma in young people in the vicinity of the petrochemical plant at Baglan Bay, South Wales, 1974 to 1991. Issue 4 (April 1995) - Lyons, R A; Monaghan, S P; Heaven, M; Littlepage, B N; Vincent, T J; Draper, G J
Abstract : OBJECTIVE--To determine whether there was an increased incidence of leukaemias and lymphomas in young people aged less than 25 years in the locality of a petrochemical plant at Baglan Bay, South Wales. METHODS--Geographical population based study to compare the observed and expected incidence of leukaemia and lymphoma with onset before the age of 25, in the years 1974 to 1991. The population was aged 0-24 years and lived within 1.5 and 3 km of the plant. The observed number of cases in various categories were compared with the expected numbers of cases calculated from the Welsh cancer registration rates. RESULTS--Although the observed numbers were generally greater than would be expected, none of the comparisons showed significant excess of leukaemias or lymphomas for any period of years. CONCLUSIONS--The study shows that the incidence of leukaemias and lymphomas in children and young people in the area around the BP Chemical site at Baglan Bay, South Wales, between the years 1974 and 1991 was not significantly greater than normal.